The Reasons and influence of the establishment of one port trade system in Guangzhou during Qing Dynasty - Yu, Zhou; Suffian Mansor,; Azlizan Mat Enh, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Guangzhou is located in the southern part of China, near the South China Sea, belongs to Guangdong Province. It serves as China's southern gateway to the world and was historically called "The Southern Treasure of the Emperor", playing a crucial role in China's maritime trade history. Throughout Chinese history, Guangzhou underwent several cycles of "closure" and "opening", policies that severely impacted trade. However, foreign merchants never ceased to request permission from the Chinese government to engage in trade. In 1757, Emperor Qianlong decreed Guangzhou as the only one official port for foreign trade. This edict led to the establishment of the one port trading system in Guangzhou, as the Qing government aimed to counter foreign influences and local uprisings while maintaining a self-sufficient small-scale agricultural economy. Western nations and their traders sought opportunities within this system, aspiring to expand trade to other regions of China, even the inland areas. The exclusive status of Guangzhou as China's only one trading port persisted until 1842, following the defeat of the Qing government in the Opium War against Britain, the Nanjing Treaty was signed. This treaty opened Guangzhou, Shanghai, Ningbo, Fuzhou, and Xiamen as trading ports, bringing an end to the one port trading system. The reasons and impacts of the establishment of this system have not been comprehensively analyzed to date. Therefore, this paper based on historical archives, analyzes both the direct and underlying reasons behind Emperor Qianlong's decision and elucidates the system's diverse impacts on various aspects of Qing-era China.